2002
DOI: 10.1143/jpsj.71.509
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Temperature Phase Diagrams of Ferroelectric Liquid Crystals

Abstract: The pressure-temperature phase diagrams of the ferroelectric liquid crystals FLC-031 and FLC-032 were obtained from the complex dielectric constant. As the pressure increases, all the transition temperatures increase. On heating, the temperature width of the smectic phase is almost independent of the pressure, while the width of the ferroelectric chiral smectic C (SmC Ã ) phases reduces with pressure and disappears at 300 MPa and 125 C for FLC-031 and 160 MPa and 102 C for FLC-032. On the other hand, the width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…When pressure was increased, the width of the SmC Ã phase became small and the SmC Ã phase finally disappeared at about 160 MPa and 133 C. This p-T phase diagram resembles the p-T phase diagrams of other FLCs. 6,7,11) Although the spontaneous polarization in some FLCs 6-8) gradually decreases with pressure, the spontaneous polarization in FLC-A showed unusual behavior with pressure. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When pressure was increased, the width of the SmC Ã phase became small and the SmC Ã phase finally disappeared at about 160 MPa and 133 C. This p-T phase diagram resembles the p-T phase diagrams of other FLCs. 6,7,11) Although the spontaneous polarization in some FLCs 6-8) gradually decreases with pressure, the spontaneous polarization in FLC-A showed unusual behavior with pressure. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the magnitude of P s as a function of reduced temperature, T À T C , is independent of pressure, where T C is the ferroelectric-paraelectric transition temperature. 5) As P S is roughly proportional to the tilt angle at atmospheric pressure, it is thought that the smooth decrease in P S under pressure [6][7][8] is caused by a decrease in tilt angle. From these phenomena, if tilt angle changes with pressure, tilt angle will show a smooth change.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The homogeneously aligned cell (about 30 µm thickness) was sealed with an epoxy resin and a room temperature vulcanizing (RTV) silicone rubber (Shin-Etsu Co., Ltd., KE-41) so that the pressure transmitting fluid (Shin-Etsu Co., Ltd., KF-96-50CS) would be prevented from entering the cell, and was mounted in a high-pressure vessel. [4] The complex dielectric constant was measured by an impedance analyzer (Solartron SI-1260) on warming. Measurement of the switching current with a triangular wave voltageg [7] was used for assigning the phase and detecting the phase transition temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In ferroelectric liquid crystals (FLCs), it has been reported that the SmC * phase narrows and vanishes with increasing pressure [3][4]. In an AFLC, however, it has been reported that the SmC * phase expands as the pressure is increased and the SmC * A phase vanishes [5].…”
Section: Introductionmentioning
confidence: 99%
“…From PVT and DTA data they observed that the temperature range of the Sm C phase diminishes with increasing pressure and above 350 MPa a new phase appears. As compared to achiral mesogens, however, only few measurements on FLCs under elevated pressure are available [2][3][4][5][6][7][8][9][10][11][12] which show that the properties of FLCs change significantly and a number of pressure driven new and interesting features are observed.…”
Section: Introductionmentioning
confidence: 99%